Støttetenester for forskingsdatahandtering på UiT Noregs arktiske universitet – erfaringar og forslag til beste praksis - Conzett, Philipp; Østvand, Lene (Nordic Journal of Information Literacy in Higher Education, 2018)
Source at https://doi.org/10.15845/noril.v10i1.283 . Accepted manuscript version, licensed CC BY-NC-ND 4.0. This article describes how support services for research data management have been developed and are run at UiT The Arctic University of Norway (UiT). We go through several areas of interest: technical solutions, researcher involvement, division of work between different units at our institution as well as co-operation with national and international stakeholders, data curation, skills development, training and curriculum development, dissemination, and policymaking. Each section concludes with a set of best practice recommendations.